Applying Co-Simulation for an Industrial Conveyor System - Bjerge, Kim; Larsen, Peter Gorm (Technical Report Electronics and Computer Engineering, 2012)
This paper describes an industrial application of a new research technology enabling the co-simulation of models in continuous time and discrete event respectively. The application concerns modeling of a conveyor system with trolleys that has tilting capabilities that can be used to compensate for high speeds in curves in order to avoid parcels falling of the trolleys. The main challenge for this kind of physical system is that a system solution here requires both insight into the mechanical physics behavior as well as ways in which the system can be controlled discretely by a software based solution. This paper demonstrates how it is possible to bridge the gap between these two different disciplines in co-simulated models.